NIAW 4114 (Phule Shashwat): A new high yielding bread wheat variety for late sown irrigated conditions of Peninsular Zone in India - Magar, Nilesh Madhavaro; Dodake, Suresh; Gadekar, Dnyandeo; Mhaske, Bhalchandra; Game, Bhanudas; Patil, Yogesh (Journal of Cereal Research, 2025)
A new bread wheat variety, NIAW 4114 (Phule Shashwat) (IC No. 653545), has been developed by the Agricultural Research Station, MPKV, Niphad. It was identified and recommended during the Varietal Identification Committee Meeting held virtually on 7th October 2024, chaired by Dr. D. K. Yadava, ADG (Seed), ICAR. In AICRP trials, this variety demonstrated a potential yield of 70.2 q ha-1 under late-sown irrigated conditions and exhibited consistent performance across the zone, ranking in the statistically superior group 16 out of 28 times. It also showed resistance to both stem and leaf rust. The variety was officially released and notified for cultivation in the Peninsular Zone of India covering Maharashtra, Karnataka, Telangana, Andhra Pradesh, and Tamil Nadu (excluding Nilgiris and Palani Hills) through notification number S.O. 2128 (E), dated 13th May 2025, by the Central Sub-Committee on Crop Standards, Notification, and Release of Varieties in India.